PENGARUH PENGETAHUAN KEWIRAUSAHAAN, LINGKUNGAN KELUARGA DAN KEPRIBADIAN WIRAUSAHA TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XII SMK SE-KABUPATEN BLORA - Muhammad Eko Nur Syafii (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2018)
This study aims to identify and analyze (1) influence knowledge entrepreneurial on interest entrepreneurship, (2) influence family environment on interest entrepreneurship, and (3) influence entrepreneurial personality on interest entrepreneurship. This research approach is quantitative descriptive. The population in this research were all students of XII class SMK in Blora regency amount to 4295 students. The sample was obtained by Cluster Random Sampling technique is 366 students. Independent variable is knowledge entrepreneurial, family environment, and entrepreneurial personality whereas dependent variable is interest entrepreneurship. Methods of data collection using questionnaire and documentation. Methods of data analysis using descriptive analysis, and multiple linier regression analysis. The results showed that (1) knowledge entrepreneurial has positive influence on interest entrepreneurship, (2) family environment has positive influence on interest entrepreneurship, and (3) entrepreneurial personality has positive influence on interest entrepreneurship